2009
DOI: 10.1074/mcp.m800410-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

A Label-free Quantitative Proteomics Strategy to Identify E3 Ubiquitin Ligase Substrates Targeted to Proteasome Degradation

Abstract: The ubiquitin-proteasome system is a central mechanism for controlled proteolysis that regulates numerous cellular processes in eukaryotes. As such, defects in this system can contribute to disease pathogenesis. In this pathway, E3 ubiquitin ligases provide platforms for binding specific substrates, thereby coordinating their ubiquitylation and subsequent degradation by the proteasome. Despite the identification of many E3 ubiquitin ligases, the identities of their specific substrates are still largely unresol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 38 publications
(42 reference statements)
1
45
0
Order By: Relevance
“…As discussed above, physical interaction screens require strong physical interactions that may depend on posttranslational modifications. Recently, cell-based functional screening approaches have been developed to identify substrates based on differential ubiquitination (14,15) or stability proteins expressed as GFP fusions (13,16) in cells where a specific E3 ligase has been mutated or inhibited. Although these approaches are immensely useful for determining the function of specific E3 ligases, they are not directly amenable for identifying the E3 ligases of a specific substrate protein of interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed above, physical interaction screens require strong physical interactions that may depend on posttranslational modifications. Recently, cell-based functional screening approaches have been developed to identify substrates based on differential ubiquitination (14,15) or stability proteins expressed as GFP fusions (13,16) in cells where a specific E3 ligase has been mutated or inhibited. Although these approaches are immensely useful for determining the function of specific E3 ligases, they are not directly amenable for identifying the E3 ligases of a specific substrate protein of interest.…”
Section: Discussionmentioning
confidence: 99%
“…However, this approach is most applicable when the E3 ligase-substrate interactions are strong and stable and may not work for transient enzyme-substrate interactions. Recently, a couple of promising large-scale approaches have been developed to identify substrates of particular E3 complexes (13)(14)(15)(16), but these approaches are not designed to identify the E3 ligases that ubiquitinate a specific protein for degradation. In fact, aside from protein interaction screening, large-scale approaches to identify how an individual protein is degraded are limited.…”
mentioning
confidence: 99%
“…We previously showed that ASB2 serves as the substrate recognition subunit of the E3 ubiquitin ligase complex that mediates polyubiquitylation and proteasomal-mediated degradation of FLNs (Baldassarre et al, 2009;Bello et al, 2009;Burande et al, 2009;Heuze et al, 2008). In order for this process to occur, FLNs and ASB2 must, at least transiently, interact.…”
Section: The Subcellular Localization Of Asb2 To Actin-rich Structurmentioning
confidence: 99%
“…We previously showed that ASB2 targets FLNa, FLNb and FLNc for proteasomal degradation (Baldassarre et al, 2009;Bello et al, 2009;Burande et al, 2009;Heuze et al, 2008) and have now mapped the ABD of FLNa as the minimal fragment sufficient for ASB2-mediated degradation. The structure of FLNaABD is highly similar to the structure of FLNbABD [root mean square deviation (r.m.s.d.)…”
Section: Asb2 Targets the Abd Of Flnb And Flnc For Degradationmentioning
confidence: 99%
“…Quantitative mass spectrometry (MS)-based proteomics is one of the most powerful tools to study the expression profiles of activated genes of interest (13,26,27). In this study, we established the proteomic and N-glycoproteomic profiles of human bronchial epithelial cell (HBEC) 1 lines that are isogenic and differ only by the presence or absence of activated KRAS.…”
mentioning
confidence: 99%